2011
DOI: 10.1007/s10753-011-9423-4
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide Enhances TNF-α-Induced IL-6 and IL-8 Synthesis in Human Proximal Renal Tubular Epithelial Cells by NF-κB-Dependent Mechanism

Abstract: Vasoactive intestinal polypeptide (VIP) is a 28-amino acid neuropeptide with vasodilator, bronchodilator, and anti-inflammatory effects. But little is known about its pro-inflammatory effects. We investigated the effect of VIP on the secretion of interleukin-6 (IL-6) and interleukin-8 (IL-8), two pro-inflammatory cytokines, in TNF-α-activated proximal renal tubular epithelial cell line (HK-2 cells). Cultured HK-2 cells were treated with TNF-α in the presence or absence of VIP with a dose range from 1 to 100 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Using VIP KO mice, different studies showed an exacerbation or an amelioration of chemically induced colitis (Abad et al, 2015; Wu et al, 2015). The notion that VIP could have both pro- and anti-inflammatory actions is not unreasonable, as VIP differentially regulates IL-6 expression, which can act as a pro- and anti-inflammatory cytokine (Huang et al, 2012). Another explanation could be due to gut microbiota structure differences as recently suggested by Wu et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using VIP KO mice, different studies showed an exacerbation or an amelioration of chemically induced colitis (Abad et al, 2015; Wu et al, 2015). The notion that VIP could have both pro- and anti-inflammatory actions is not unreasonable, as VIP differentially regulates IL-6 expression, which can act as a pro- and anti-inflammatory cytokine (Huang et al, 2012). Another explanation could be due to gut microbiota structure differences as recently suggested by Wu et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lipofectamine Transfection Reagents (Invitrogen) were used. After transfection as previously described [ 34 ], cells were cultured overnight and treated with 10ng/ml TNF-α in the presence or absence of Mefunidone (0.06, 0.12, and 0.18mM) or DXM (10 -6 M) as positive control. Luciferase activity was assessed using a luciferase assay substrate (Promega) according to manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…found that VIP increases TNF‐α‐induced production of IL‐6 and IL‐8 via activating the NF‐κB pathway in human proximal renal tubular epithelial cells (Huang et al . ). Moreover, it was also reported that VIP increases pro‐inflammatory osteotropic cytokines such as IL‐6 in an osteoblastic cell line (Persson & Lerner ).…”
Section: Discussionmentioning
confidence: 97%
“…However, VIP was also reported to enhance IL-6 secretion in unstimulated peritoneal macrophages as early as in the 1990s (Martinez et al 1998b). Ling et al found that VIP increases TNF-a-induced production of IL-6 and IL-8 via activating the NF-jB pathway in human proximal renal tubular epithelial cells (Huang et al 2012). Moreover, it was also reported that VIP increases pro-inflammatory osteotropic cytokines such as IL-6 in an osteoblastic cell line (Persson & Lerner 2005).…”
Section: Discussionmentioning
confidence: 99%